Recent Advances in Systems Safety and Security - Pricop, Emil.; Stamatescu, Grigore; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book represents a timely overview of advances in systems safety and security, based on selected, revised and extended contributions from the 2nd and 3rd editions of the International Workshop on Systems Safety and Security - IWSSS, held in 2014 and 2015, respectively, in Bucharest, Romania. It includes 14 chapters, co-authored by 34 researchers from 7 countries. The book provides an useful reference from both theoretical and applied perspectives in what concerns recent progress in this area of critical interest. Contributions, broadly grouped by core topic, address challenges related to information theoretic methods for assuring systems safety and security, cloud-based solutions, image processing approaches, distributed sensor networks and legal or risk analysis viewpoints. These are mostly accompanied by associated case studies providing additional practical value and underlying the broad relevance and impact of the field.
The Theory of Witness Functions -- Quantification of Centralized/Distributed Secrecy in Stochastic Discrete Event Systems -- Framework for Cognitive Radio Deployment in Large Scale WSN-UAV Surveillance -- Using Modeling and Dynamic Simulation Techniques for Systems' Safety and Security -- HAZOP-based Security Analysis for Embedded Systems: Case Study of Open Source Immobilizer Protocol Stack -- Multimodal Heterogeneous Monitoring Of Super-Extended Objects: Modern View -- Image Based Control of a Simple Mobile Robotic System -- On using a Cloud-Based Approach to Develop a Mobile Asset Management Solution -- Execution of an IEC61499 Application on a Remote Server -- Evolution of Legal Issues of Honey nets -- A Risk Screening System by Network Diagram Recognition for Information Security Audit -- Risk Analysis and Optimal Model for Efficiency of Reengineering the Independent Power Grids -- Innovative Fuzzy Approach on Analyzing IndustrialControl Systems -- IPv6 Sensor Networks Modeling for Security and Communication Evaluation.
Keywords: Computational intelligence; Telecommunication; Data protection; Computational Intelligence; Communications Engineering, Networks; Data and Information Security